2020
DOI: 10.4103/jcd.jcd_561_20
|View full text |Cite
|
Sign up to set email alerts
|

Micro-computed tomographic analysis of the marginal adaptation of a calcium silicate-based cement to radicular dentin after removal of three different intracanal medicaments - An in vitro study

Abstract: Context: This study focuses on the marginal adaptation of a calcium silicate-based cement to the root dentin after retrieval of different intracanal medicaments. Aim: This study compared the marginal adaptation of a calcium silicate-based cement to radicular dentin in the apical third of the root canal following the use of three different intracanal medicaments. Materials and Methods: Forty single-rooted premolar teeth ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Only a limited number of previous studies have used the same methodology to quantitatively assess the volume of interfacial gaps and inner porosity of selected CSCs applied as root-end filling materials. Some of them evaluated the loss of volume and density of tested CSCs exhibited after exposure to acidic or alkaline conditions, blood, or after retrieval of various intracanal medicaments, along with their marginal adaptation [25][26][27][28]. Given the differences in the study designs, our results were compared only with those obtained in similar experimental conditions, i.e., after material immersion in distilled water or in normal saline only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a limited number of previous studies have used the same methodology to quantitatively assess the volume of interfacial gaps and inner porosity of selected CSCs applied as root-end filling materials. Some of them evaluated the loss of volume and density of tested CSCs exhibited after exposure to acidic or alkaline conditions, blood, or after retrieval of various intracanal medicaments, along with their marginal adaptation [25][26][27][28]. Given the differences in the study designs, our results were compared only with those obtained in similar experimental conditions, i.e., after material immersion in distilled water or in normal saline only.…”
Section: Discussionmentioning
confidence: 99%
“…Only Jardine et al [27] reported a higher rate of porosity with Biodentine than MTA-Angelus. According to micro-CT investigations, Biodentine demonstrated a TPV% within a range of 2.48-6.66% and external porosity volume percentage (EPV) between 0.616-3.78%, and CPV% varied between 0.024-4.46% [23][24][25][26][27][28]. Only Toia et al [32] reported an unusually high porosity percentage of 50.45%, making this result difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%